Wastewater surveillance in the military: how deployed members of the armed forces can monitor outbreaks on military vessels - Gitter, Anna; Mena, Kristina D.; Crum, Michelle; Butler, Erick (Frontiers in Epidemiology, 2026)
This perspective piece explores the potential to implement wastewater surveillance on military vessels to improve disease monitoring and prevention. We examine five key topics: (1) recent studies of wastewater surveillance on military bases and training centers; (2) best practices for confined populations (e.g., colleges, prisons, hospitals, and low-income and middle-income countries) and their transferability to military settings; (3) current technologies enabling deployed personnel to conduct wastewater surveillance without advanced microbiological training; (4) key questions the military should address to prevent future outbreaks on vessels; and (5) unique ethical considerations surrounding implementation. This work aims to inform military decision-makers considering the adoption of wastewater surveillance programs.